2015
DOI: 10.1016/j.tox.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenic expression of human carboxylesterase-2 and cytochrome P450 3A4 in liver and duodenum: Postnatal surge and organ-dependent regulation

Abstract: Human carboxylesterase-2 (CES2) and cytochrome P450 3A4 (CYP3A4) are two major drug metabolizing enzymes that play critical roles in hydrolytic and oxidative biotransformation, respectively. They share substrates but may have opposite effect on therapeutic potential such as the metabolism of the anticancer prodrug irinotecan. Both CES2 and CYP3A4 are expressed in the liver and the gastrointestinal tract. This study was conducted to determine whether CES2 and CYP3A4 are expressed under developmental regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 41 publications
(72 reference statements)
4
31
0
Order By: Relevance
“…In a limited number of liver tissue samples from children between 0 and 10 years of age, the observed CES1 protein expression was 4-fold lower than that in adult samples (Yang et al, 2009). Consistent with our data, Shi et al (2011) and Chen et al (2015) have also reported age-dependent relative changes in CES1 and CES2 hepatic activity. The suggested variability in age-dependent CES1 protein expression level is confirmed in this study and compared with the adult data.…”
Section: Discussionsupporting
confidence: 90%
“…In a limited number of liver tissue samples from children between 0 and 10 years of age, the observed CES1 protein expression was 4-fold lower than that in adult samples (Yang et al, 2009). Consistent with our data, Shi et al (2011) and Chen et al (2015) have also reported age-dependent relative changes in CES1 and CES2 hepatic activity. The suggested variability in age-dependent CES1 protein expression level is confirmed in this study and compared with the adult data.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with this expectation, Shi et al (2011) reported an approximate 2-fold increase in mean relative CES1 protein levels in hepatic S9 fractions from donor samples between 5 weeks and 6.5 months of age and adults (.18 years of age). Similar results have recently been reported for CES2 (Chen et al, 2015).…”
Section: Hines Et Alsupporting
confidence: 92%
“…The same holds true for CYP3A4 mRNA expression where a significantly higher mRNA expression has been found in young adults but also a much higher expression in the first year of life as compared to 1‐ to 6‐ and 6‐ to 17‐year‐olds. Recent data show the level of liver CYP3A4 mRNA to be positively correlated with age, whereas duodenal CYP3A4 mRNA showed a more complex and almost opposite pattern …”
Section: Absorption Of Drugsmentioning
confidence: 99%
“…It was shown that intestinal GST participates in the first‐pass extraction of this drug, showing an upregulated activity in children younger than 5 years of age . Chen and colleagues measured CES2 mRNA and protein in duodenal samples from human donors of various ages and showed an increase with advancing age, reaching adult values at 0.5‐1 year of age. However, despite this developmental pattern of intestinal CES2, the prodrugs candesartan cilexetil and olmesartan medoxomil showed the same PK profile after oral dosing in children as in adults …”
Section: Absorption Of Drugsmentioning
confidence: 99%